Transit-oriented development and transportation equity in mid-sized midwestern cities: a case study of Cleveland, Ohio - Massey, Haley (My University, 2026)
Transit-oriented development (TOD) aims to reduce car dependence, promote sustainable land use practices, and enhance mobility options. However, questions remain about whether TOD equitably serves diverse populations, especially in mid-sized Midwestern cities shaped by deindustrialization and car-centric planning. This study examines Cleveland, Ohio’s HealthLine bus rapid transit (BRT) corridor to evaluate how TOD affects transportation equity. The analysis uses a descriptive case study method, reviewing policy documents, AllTransit metrics, and Census data. The findings show that the HealthLine improved transit accessibility, connected residents to more than 180,000 jobs within a 30-minute commute, and spurred $9.5 billion in corridor investment. Households near the HealthLine exhibited higher rates of transit commuting and lower car ownership than citywide averages. Yet, equity outcomes proved uneven. Early TOD policies prioritized economic development over equity protections, with affordable housing or anti-displacement measures introduced only after development pressures intensified. While many low-income and Black residents live within the corridor and gained improved access, gentrification and affordability concerns limited the reach of these benefits. This research finds that while TOD increases transit access and spurs reinvestment in mid-sized Midwestern cities, equity is not guaranteed. Embedding equity as a guiding principle from the outset, through affordable housing, inclusive zoning, and equity-focused transit policies, is necessary if TOD is to meet its promise of equitable urban mobility.
Keywords: Transit-oriented development; Equity; Cleveland; Healthline; Accessability; Transportation